The promise of unbroken straw - Steele, Ken (Yorkshire Publishing, 2024)
"1944, Oklahoma. With their family farm on the brink of ruin, Paul 's life takes an unexpected turn--but newfound fortune comes at anunimaginable cost."--Provided by publisher.